ANALISIS SWOT BERBASIS DATA RAPORT PENDIDIKAN DALAM PERUMUSAN STRATEGI PENINGKATAN MUTU SD NEGERI 001 PULAU DERAWAN - Rizki Gagah Perkoso; Dedy Hartanto; Juliansyah; Herwin; Muhamad Guntur; Nurlaili; Usfandi Haryaka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to analyze the educational quality of SD Negeri 001 Pulau Derawan based on Education Report data using a SWOT analysis approach as the basis for formulating school quality improvement strategies. The study was motivated by the low literacy and numeracy achievement of students and the suboptimal utilization of Education Report data in data-based school planning. This research employed a qualitative descriptive approach. The data were collected through observation and document analysis of the 2023 Education Report of SD Negeri 001 Pulau Derawan. Data analysis was conducted using SWOT analysis by identifying the school’s strengths, weaknesses, opportunities, and threats based on educational quality indicators and field conditions. The results showed that the school’s strengths lie in school safety climate, student character, inclusivity climate, and the principal’s instructional leadership. Meanwhile, the main weaknesses include low literacy and numeracy achievement, basic-level learning quality, and limited learning facilities. The opportunities available include the Merdeka Belajar policy, School Operational Assistance (BOS) funding, the Merdeka Mengajar Platform, and local government support. The main threats consist of geographical limitations of the island area, high teacher turnover, and limited internet access. Based on the SWOT analysis, several quality improvement strategies were formulated, focusing on strengthening literacy and numeracy, improving teacher competence, optimizing contextual learning based on local potential, and strengthening collaboration between schools and the community.